2015
DOI: 10.1371/journal.pone.0140694
|View full text |Cite
|
Sign up to set email alerts
|

TIM-3 Suppresses Anti-CD3/CD28-Induced TCR Activation and IL-2 Expression through the NFAT Signaling Pathway

Abstract: TIM-3 (T cell immunoglobulin and mucin-domain containing protein 3) is a member of the TIM family of proteins that is preferentially expressed on Th1 polarized CD4+ and CD8+ T cells. Recent studies indicate that TIM-3 serves as a negative regulator of T cell function (i.e. T cell dependent immune responses, proliferation, tolerance, and exhaustion). Despite having no recognizable inhibitory signaling motifs, the intracellular tail of TIM-3 is apparently indispensable for function. Specifically, the conserved r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 51 publications
2
44
0
Order By: Relevance
“…Though it is has been demonstrated that signaling through both PD-1 and TIM-3 diminish T cell responses by regulating transcription factor activity, it remains to been seen how this signaling is qualitatively different than the inhibitory signaling that occurs with T cells possessing a chronically dysfunctional phenotype. 26,27 We hope these results will stimulate further investigation into the differences between infection and tumor-induced expression of inhibitory receptors and serve as a potentially cautionary result for use of immune checkpoint inhibitors in contexts which may not reflect clinically analogous situations. Therefore, it will be important to appreciate these differences in future studies of combinations of oncolytic virotherapy with checkpoint inhibitor blockade.…”
Section: Discussionmentioning
confidence: 96%
“…Though it is has been demonstrated that signaling through both PD-1 and TIM-3 diminish T cell responses by regulating transcription factor activity, it remains to been seen how this signaling is qualitatively different than the inhibitory signaling that occurs with T cells possessing a chronically dysfunctional phenotype. 26,27 We hope these results will stimulate further investigation into the differences between infection and tumor-induced expression of inhibitory receptors and serve as a potentially cautionary result for use of immune checkpoint inhibitors in contexts which may not reflect clinically analogous situations. Therefore, it will be important to appreciate these differences in future studies of combinations of oncolytic virotherapy with checkpoint inhibitor blockade.…”
Section: Discussionmentioning
confidence: 96%
“…Many factors are known to regulate Th1 and Th2 differentiation, especially renin-angiotensin system (RAS). A growing body of evidence suggests that anti-CD3/CD28 treatment also induces Th1 differentiation reflected by upregulation of IL-2, IFN-α and NF-kB activity in Jurkat cells or in human CD4 + T cells [19, 20]. Many factors are known to regulate Th1 and Th2 differentiation, including renin-angiotensin system (RAS).Ang II, a major effector of RAS, plays a critical role in this process.…”
Section: Discussionmentioning
confidence: 99%
“…The phosphorylated tyrosines within the cytoplasmic domain of TIM-3 can then recruit p85 adaptor protein, leading to the activation of PI3 kinases. TIM-3 has also been shown to inhibit TCR proximal signaling [47,48]. In TIM-3 + CD8 + effector T cells, Gal-9 is shown to induce co-localization of TIM-3 with receptor phosphatases CD45 and CD148, and thereby inhibits TCR signaling [49].…”
Section: Molecular Characteristics Of Tim-3 Its Ligands and Signmentioning
confidence: 99%